Interactive Videodisc as an Instructional Tool in Medical Education - Culbert, A. J., Jr.; Cantelmo, Nancy L.; Stafford, Mary E.; Allan, D. M. E. (Methods of Information in Medicine, 1989)
At a time when medical educators are actively revising the undergraduate medical school curriculum to make it more responsive to exigencies ofthe 21st century, the use of interactivevide.odisc technology may well prove to be a significant addition. Using interactive videodisc technology may be instrumental in reducing the amount of a large lecture didactic learning and improving small group problem-solving sessions that better synthesize factual knowledge. It also provides important and valuable exposure to varieties of computer technology that play an increasingly important role in training and medical practice.
Keywords: Interactive Videodisc; Education; Curriculum